Evaluation of Students’ Educational Management Quality Based on Intuitionistic Fuzzy Information - Fangjian Cao (Advances in Multimedia)
In order to further improve the scientificity and rationality of students’ education management quality evaluation, this paper proposes a method of students’ education management quality evaluation based on intuitive fuzzy information. This method makes a scientific judgment on the teaching management process and teaching results in combination with the objectives of students’ education and teaching management. On the basis of teaching evaluation, with the help of intuitionistic fuzzy information integration algorithm method, this paper focuses on using intuitionistic fuzzy-weighted average operator and normal distribution weighting method to construct the quality evaluation model of students’ education and teaching management, and develops the teaching quality evaluation system based on intuitionistic fuzzy theory. Through the two-level fuzzy comprehensive evaluation, the teacher evaluation result score is 81.45, which is an algebraic value from 0 to 100, and the score is between 80 and 90, which verifies that the classroom teaching evaluation result is good.